Visual evoked potential: a diagnostic tool for the assessment of hepatic encephalopathy. Issue 3 (March 1984) - Zeneroli, M L; Pinelli, G; Gollini, G; Penne, A; Messori, E; Zani, G; Ventura, E
Abstract : Visual evoked potential recordings were examined in 45 liver cirrhosis patients with (n = 29) and without (n = 16) encephalopathy, in 15 normal volunteers, and in one patient with an opioid induced stupor state. Visual evoked potential parameters were classified on the basis of EEG recordings. Plasma concentrations of amino acids, octopamine, and ammonia were assayed in order to document the metabolic change of hepatic encephalopathy. Latencies and wave patterns recorded after flash stimulation differentiated the four degrees of the coma one from another according to EEG classification in the 29 patients with encephalopathy. In the group of 16 patients without clinical and EEG evidence of encephalopathy the visual potential recordings discriminated a group of patients (n = 10) in a preclinical stage of encephalopathy. Biochemical parameters and subsequent clinical observation of patients confirmed our judgement of a preclinical stage of encephalopathy. These results suggest that visual evoked potentials are a simple, suitable and objective method for differentiating the degrees of encephalopathy and for identifying the preclinical stage of encephalopathy.